Conceptual Understanding and Critical Thinking Skills Assisted by a Virtual Laboratory through Guided Inquiry Learning - Rahma, Dinda Maulidhatul; Yuliati, Lia; Nasikhudin (Kasuari: Physics Education Journal (KPEJ), 2025)
This study aims to determine the effect of the guided inquiry learning model on students' conceptual understanding and critical thinking skills in physics, with the support of a virtual laboratory, among Grade X students at SMAN 1 Situbondo in the 2023/2024 academic year. The main problem in learning physics is the low ability of students to understand concepts in depth and develop critical thinking about scientific phenomena. The guided inquiry learning model was chosen to create systematic learning, allowing students to explore, observe and draw conclusions. Meanwhile, virtual laboratories are used as supporting media to simulate experiments that cannot be carried out directly due to limited facilities and time. The type of research used is an experimental study with a posttest-only control group design. The population in this study consisted of Grade X Science Program (MIA) students, comprising three classes with 30 students each. The sample was selected using the cluster random sampling technique. The data collection instrument was an essay test to measure conceptual understanding and critical thinking skills. Data were analyzed using the MANOVA test. The analysis results showed that the calculated F value was more significant than the F table value, indicating that the guided inquiry learning model had a significant effect on students' conceptual understanding and critical thinking skills in physics when using a virtual laboratory for Grade X students at SMAN 1 Situbondo in the 2023/2024 academic year.